CALCAREOUS NANNOFOSSILS AT THE TRIASSIC/JURASSIC BOUNDARY: STRATIGRAPHIC AND PALEOCEANOGRAPHIC CHARACTERIZATION (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2016)
In this work, calcareous nannofossils are identified for the first time in the uppermost Triassic sequence of the Lombardy Basin (Southern Calcareous Alps, Italy). Two zones are recognized, namely the NT2b (latest Triassic) and the NJT1 (earliest Jurassic). Two species resulted to be good markers to constrain the TJB interval: Prinsiosphaera triassica and Schizosphaerella punctulata. Nannofossil data are calibrated with C isotopic chemostratigraphy obtained for carbonate and organic matter. Size reduction of P. triassica and a decline in the abundance of Triassic nannofossils are detected soon after the “precursor Carbon Isotope Excursion (CIE) and culminated during the “initial negative CIE” characterized by lowest nannofossil abundances and small-sized P. triassica. The extinction of Triassic nannofossils occurred in distinctive steps within the “initial negative CIE”, while the Jurassic S. punctulata is first observed at the base of the “main negative CIE”. The latest Triassic nannofossil decline in abundance, size reduction and extinctions, represent a progressive deterioration associated to the Central Atlantic Magmatic Province (CAMP) volcanism. Our findings are consistent with nannofossil changes at supraregional scale and indicate that the massive CAMP flood basalts were preceded by initial volcanic pulses. We speculate that a combination of climate change, fertilization and ocean acidification started to influence the calcification process prior to the “initial negative CIE”. Nannoplankton extinctions were not simultaneous and might imply limited capacity for adaptation in the early stages of evolutionary history. However, originations of new taxa soon after the disappearance of Triassic forms suggest the ability to rapidly overcame extreme stressing conditions.